AHMAD JAAM'S MYSTICAL, MORAL AND PHILOSOPHICAL THOUGHTS - Karomatullo Olimov; Saeid Yoosefisoorany (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
If we look through the history of mankind, we will realize that this planet has been the birthplace of human beings who by presenting their valuable thoughts have created changes in the life of humanity. One of them is Ahmad Jaam, who Less attention has been paid to introducing his moral, philosophical and philosophical thoughts, which this has led to the failure to identify and introducing him in some of the important books of theosophical men and Iranian thinkers. Therefore, this article prompted the introduction of his thoughts and mentality. Ahmad Jaam is a social thinker and reformer and a righteous Sufi and pure believer, a liberated man with ethical and philosophical and Shari'ah mystical thoughts who believes seeking the guidance of the Shari'ah as a way of treating moral diseases in the community. He is the advocate of establishing the justice in society and creation of unity among peoples and with the spirit that is devoid of any religious prejudice, put the basis on peace and compromise with the followers of all religions and sects. He looks the same at Zoroastrianism, Christian, Jew and Idolater, and Muslim. And he writes, "Submissive of anywhere is dear. It may be among the Zoroastrianism and the Jew and Christian and the wicked wherever are wicked, if it is in the Kaaba". He spent most of his life on the awakening of the audience and in a fight against ignorance and Sufi seeming of the Khanqaha, cortical mystics and erudite seeming of his era.